IMPLEMENTASI PROGRAM MAHANANNI DALAM PENATAAN KUMUH BANTARAN SUNGAI CODE KOTA YOGYAKARTA - Lean S, Fernanda; Supardal, Supardal (Penerbit Lafadz Jaya, 2026)
Yogyakarta City continues to face urban slum challenges, particularly along riverbanks, which undermine housing adequacy, environmental health, and residents’ sense of safety. A priority area is the Code Riverbank in Terban Subdistrict, Gondokusuman, characterized by high density, limited basic infrastructure, and exposure to disasters. The City Government implemented the MAHANANNI Program as an area-based slum upgrading innovation through land consolidation (including on Sultan ground land), basic infrastructure upgrading, and community institutional strengthening. This study analyzes the implementation of the MAHANANNI Program in improving the quality of life of Code riverbank residents in Terban. A descriptive qualitative approach was used with purposive sampling; data were collected through observation, in-depth interviews, and documentation and validated through source triangulation. The findings indicate that MAHANANNI reached its primary targets through in-situ interventions—rehabilitation, rejuvenation, and land consolidation—supported by community deliberation forums. Early outcomes showed improvements in environmental quality and health, reflected in full coverage of adequate ventilation and sanitation and declining diarrhea and acute respiratory infection cases. However, stronger cross-agency coordination, integration of economic empowerment components, and a unified beneficiary database are required to ensure the sustainability of area-based upgrading.